A Escravidão nas Propriedades Jesuíticas: Entre a caridade cristã e a violência - Assunção, Paulo de (Acervo, 2011)
A B S T R A C T In his article the author exposes how the jesuits in the various properties of the Jesus Company regarded the slaves. The discourse of some religious tended toward the defense of the humanitary treatment, following the christian precepts of charaty, not denying or questioning, however, the established system of slavery, assuming it as natural and necessary to the development of society. The practice proved that many of them did not pursue those precepts, making use of mecanisms of punishment and violence in their treatment of slaves.